Smartphone photography as a possible method of post-validation trachoma surveillance in resource-limited settings. Issue 6 (22nd July 2019) - Snyder, Blake M; Sié, Ali; Tapsoba, Charlemagne; Dah, Clarisse; Ouermi, Lucienne; Zakane, S Alphonse; Keenan, Jeremy D; Oldenburg, Catherine E
Abstract: Background: Validation of trachoma elimination requires monitoring after discontinuation of trachoma program activities, though such evaluations are not commonly done. Methods: Conjunctival examinations and smartphone photography were performed on a random sample of pre-school children from 15 villages in a region of Burkina Faso thought to have eliminated trachoma. Results: No clinically active trachoma was detected by in-field or photographic evaluation. Smartphone images demonstrated high agreement with field grading (>99% concordance). Conclusions: Trachoma appears to have been eliminated from this area of Burkina Faso. Smartphone cameras may be a useful aid for monitoring in resource-limited settings.